Cross sections in the 2 nu(5) band of formaldehyde studied by cavity enhanced absorption spectroscopy near 1.76 mu - Barry, H; Corner, L; Hancock, G; Peverall, R; Ritchie, G (2002)
The 2v5 C-H stretching band of formaldehyde has been studied by cavity enhanced absorption spectroscopy near 1.76 μm using the output of an external cavity diode laser. Strong individual transitions have been spectroscopically identified, and the absorption cross section and air broadening parameter measured for the QR1(10) line at 5676.21 cm-1, a wavenumber at which interference from absorption by atmospheric CH4 and other constituents is minimal. The integrated cross section is found to be 5.7 ± 0.6 × 10-22 cm2 cm-1, and the pressure broadening coeficient for air at 295 K is 3.93 MHz Torr-1 (half width at half maximum of the Lorentzian component). The integrated intensity of the 2v5 absorption band is found to be a factor of 108 smaller than that of the v5 fundamental. Implications of these values for the measurement of atmospheric formaldehyde by absorption near 1.76 μm are discussed.